The analysis of varietal structure of maize cultivated for grain in the Rostov region - Yu. B. Arzhenovskaya (Зерновое хозяйство России)
The current stage of plant growing is characterized by varietal policies aimed at increasing the number of new varieties (hybrids) being bred for production. This feature of varietal diversity makes it possible to choose a variety (hybrid) for specific forecrops and soil-climatic conditions, a variety with specific adaptability, length of vegetation period and product quality. One of the largest regions of the maize sown area in Russia is the Rostov region, the conditions of which allow cultivating maize with different ripening periods. The current paper has presented the dynamics of the maize productivity in Russia and in the Rostov region. There has been conducted an analysis of sown maize hybrids and varieties in the Rostov region according to the year of including them into the State List of the Russian Federation. It has been determined that the largest number of maize hybrids was cultivated in 2018 from the number included into the State List of the Russian Federation for the period from 2009 to 2013 (52 pcs.), and in 2019 from the number included into the State List of the Russian Federation for the period from 2010 to 2014 (57 pcs.). There has been demonstrated a share of maize hybrids in the sown area depending on their time being in production. So, the hybrids that have been cultivated for 6–10 years occupied the largest share (44.6% in 2018; 52.6% in 2019). There have been identified the most popular maize hybrids cultivated in the Rostov region in 2018 and 2019. There has been calculated a share of domestic hybrids (varieties) in the sown areas and the cost advantage of domestic maize seeds.